A novel cold biorefinery approach for isolation of high quality fish oil in parallel with gel-forming proteins. (1st December 2020) - Abdollahi, Mehdi; Undeland, Ingrid
Highlights: A multiple product biorefinery approach was developed for fish by-products. Fish oil was extracted from by-products parallel with gel-forming proteins at ≤10 °C. Cold-produced oils had higher amounts of LC n-3 PUFA compared to heating method. Alkaline pH-shift processing produced oils with remarkably less oxidation products. Abstract: The pH-shift process for isolation of gel-forming proteins from fish processing by-products was extended to allow parallel isolation of fish oil. Subjecting the floating emulsion layer formed during pH-shift processing of salmon by-products to pH-adjustment or freeze/thawing efficiently released the emulsified oil at 4 °C. However, for herring by-products higher temperature (10 °C) and a combination of the emulsion-breaking techniques was required for efficient oil release. Oil recovery yield using the adjusted pH-shift process was lower than with classic heat-induced oil isolation (90 °C/20 min), but pH-shift-produced oils had higher amounts of n-3 polyunsaturated fatty acids (n-3 PUFA). Also, alkaline pH-shift processing produced oils with remarkably less oxidation products and free fatty acids compared with acid pH-shift process or heat-induced isolation. Extending the pH-shift process with emulsion breaking techniques can thus be a promising biorefinery approach for parallel cold production of high-quality fish oil and gel-forming proteins from fish by-products.